(untitled) (Research, Society and Development, 2023)
Introduction: Known as electronic cigarettes, Electronic Smoking Devices (ESDs) have gained popularity as a less harmful alternative to conventional cigarettes. One of the most damaging consequences of smoking on oral health is periodontitis, but it is not yet clear what impact ESDs can have on periodontal structures. Aim: to identify what damage the use of electronic cigarettes can cause to the periodontal structure, comparing the periodontium of people who use electronic cigarettes, traditional cigarettes and non-smokers. Methodology: integrative literature review in the PubMed database carried out between April and May 2023, with the elaboration of the research question and the search strategy using the PICo strategy. As inclusion and exclusion criteria, there were no chronological or language restrictions, and those that corresponded to the theme and the guiding question were eligible. The search and article selection stages were based on the Prisma flowchart. Of the 54 studies found, nine were included. Results: E-cigarette smokers had a worse periodontal situation than non-smokers, but with milder injuries compared to conventional smokers. Bleeding on probing was lower, but plaque accumulation was higher. The likelihood of increased periodontal inflammation and levels of pro-inflammatory cytokines is higher than in non-smokers. Conclusion: The effects of e-cigarettes reported in this review are not sufficient to clearly identify the periodontal damage caused by them, but the results point to a worsening of periodontal health with long-term exposure.